2010
DOI: 10.1007/s00411-010-0311-3
|View full text |Cite
|
Sign up to set email alerts
|

Current status of biodosimetry based on standard cytogenetic methods

Abstract: Knowledge about dose levels in radiation protection is an important step for risk assessment. However, in most cases of real or suspected accidental exposures to ionizing radiation (IR), physical dosimetry cannot be performed for retrospective estimates. In such situations, biological dosimetry has been proposed as an alternative for investigation. Briefly, biodosimetry can be defined as individual dose evaluation based on biological endpoints induced by IR (so-called biomarkers). The relationship between biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 101 publications
0
56
0
Order By: Relevance
“…Over the past decades, the most commonly used method in biological dosimetry was cytogenetic analysis, in which the stable (translocations) and unstable (dysenteric chromosomes, micronuclei) chromosomal aberrations are counted in peripheral blood lymphocytes, along with a few other methods such as the glycophorin A mutation assay, electron paramagnetic resonance in tooth enamel, and the comet assay [69; 70]. However, cytogenetic analysis is time-consuming; it implies growth stimulation for 48–72 hrs since chromosomal damage can only be measured in metaphases [71]. Thus, such an analysis is not suitable for the rapid identification of the most severely exposed individuals, which is required in the event of a large-scale radiation emergency, when reliable detection is needed for population triage during the first few hours after accidental radiation exposure.…”
Section: Biodosimetrymentioning
confidence: 99%
“…Over the past decades, the most commonly used method in biological dosimetry was cytogenetic analysis, in which the stable (translocations) and unstable (dysenteric chromosomes, micronuclei) chromosomal aberrations are counted in peripheral blood lymphocytes, along with a few other methods such as the glycophorin A mutation assay, electron paramagnetic resonance in tooth enamel, and the comet assay [69; 70]. However, cytogenetic analysis is time-consuming; it implies growth stimulation for 48–72 hrs since chromosomal damage can only be measured in metaphases [71]. Thus, such an analysis is not suitable for the rapid identification of the most severely exposed individuals, which is required in the event of a large-scale radiation emergency, when reliable detection is needed for population triage during the first few hours after accidental radiation exposure.…”
Section: Biodosimetrymentioning
confidence: 99%
“…Dose-response curves have shapes and slopes that differ as a function of LET and relative biological effectiveness [17]. For low-LET radiation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to the IAEA [11], each laboratory must have its own dose-response curve, since several factors can influence the dose-effect relationships such as culture conditions or dicentric scoring efficiency [2,3,[12][13][14][15][16]. The main advantages of scoring dicentrics is its high specificity for ionizing radiation, low background in non-exposed populations (about 1 dicentric per 1000 cells) and a low detection limit, about 0.1 Gy for low-LET radiation if 500-1000 metaphases are scored [6,11,17,18]. Studies on both lowand high-LET radiation demonstrated that exposures in vitro and in vivo produce similar yields of dicentrics per unit dose [6,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic assays are the most extensively used biodosimetry assays, such as premature chromosome condensation (PCC) assay, micronuclei formation scoring, translocation and dicentric assay together [48]. Dicentric assay is currently the gold standard dosimetric method.…”
Section: Toward the Automation And Integration Of Assay Chemistries Fmentioning
confidence: 99%